Four-fermion production in e+e- collisions at centre-of-mass energies of 130 and 136 GeV - BUSKULIC, D. (Institutional Knowledge at Singapore Management University, 1996)
Four-fermion events have been selected in a data sample of 5.8 pb−1 collected with the aleph detector at centre-of-mass energies of 130 and 136 GeV. The final states ℓ+ℓ−qq, ℓ+ℓ−ℓ+ℓ−, ννqq, and ννℓ+ℓ− have been examined. Five events are observed in the data, in agreement with the Standard Model predictions of 6.67±0.38 events from four-fermion processes and 0.14−0.05+0.19 from background processes.